PENGARUH MEDIA VIDEO ANIMASI TENTANG KONSUMSI BUAH DAN SAYUR TERHADAP PENGETAHUAN SISWA SEKOLAH DASAR (Jurnal Kesehatan Siliwangi, 2021)
Low consumption of fruits and vegetables in elementary school age children at the age of 5 years. The proportion of consumption of vegetables and fruits less than 5 servings a day at the age of 5 years nationally is 95.5%. Meanwhile, for the Province of West Java, the proportion of consumption of vegetables and fruits is less than 5 portions a day at the age of ≥ 5 years, which is very high above the national proportion of 98.2%. Due to the lack of consumption of fruits and vegetables, it is necessary to provide intervention in order to increase knowledge and consumption of vegetables and fruits. The purpose of this study is to produce a media that is feasible and can be used as a medium for Health Promotion in increasing consumption of Fruits and Vegetables, so as to determine the effect of animated video media on fruit and vegetable consumption on the knowledge of elementary school students. This study used a quasi-experimental design with a one group pretest-posttest design on 29 students. Collecting data using a questionnaire measuring instrument via google form. Data analysis was univariate and bivariate. The results of the study showed the average value of knowledge before the intervention was 70.68, while after the intervention was 81.60. The results of the paired t-test obtained p value 0.000 <0.05, so it can be concluded that the animated video media about fruit and vegetable consumption affects the knowledge of elementary school students.